Data for 'Multistable Nematic Wells: Modelling Perspectives, Recent Results and New Directions' - Majumdar, A; Lewis, A (University of Oxford, 2016)
This folder contains 15 data sets in .dat format and two matlab programs. The datasets are generated by using an arrayfun on EnergyCalculation.m. Examples of how to generate these sets are given in Sec1_NormalizedEnergies.m. Sec1_NormalizedEnergies.m also contains information on generating plots of the energy landscape, the energy barriers and energies along optimal pathways from these datasets